Healthcare use in the year preceding a diagnosis of pancreatic cancer: a register-based cohort study in Denmark - Linda A. Rasmussen; Line F. Virgilsen; Claus W. Fristrup; Peter Vedsted; Henry Jensen (Taylor & Francis Group, 2022)
AbstractObjective To describe the use of healthcare prior to a diagnosis of pancreatic cancer in Denmark.Design A population-based cohort study using prospectively recorded data from Danish National Health Registries.Setting Danish general practice and hospitals.Subjects A total of 5926 patients diagnosed with pancreatic cancer in 2012-2018 and 59,260 matched references without pancreatic cancer from the Danish general population.Main outcome measures The monthly frequency of healthcare use (contacts and tests in general practice and contacts and diagnostic investigations in hospitals) during the 12 months preceding the pancreatic cancer diagnosis and a corresponding index date assigned to the references.Results Compared to the references, the patients had increased contacts and diagnostic tests, especially blood glucose testing, in general practice from 7 to 12 months before diagnosis. Hospital contacts and diagnostic imaging increased from 5 months before the diagnosis.Conclusions The pattern of increasing healthcare contacts before a diagnosis of pancreatic cancer may represent a window of opportunity to diagnose pancreatic cancer earlier. The increased use of blood glucose test in general practice may represent an important sign of an underlying disease. Key pointsPancreatic cancer is a rapidly progressing and highly lethal disease. Focus on early diagnosis is essential to improve the prognosis.Patients with pancreatic cancer had increased number of healthcare contacts from 7 months before the diagnosis.Patients with pancreatic cancer had increased number of blood glucose tests taken throughout almost the entire year before the diagnosis.The results may indicate that a window of opportunity exists to diagnose pancreatic cancer earlier.